Ensembl 2023. Issue Volume 51:Issue D1(2023) (1st November 2022) - Martin, Fergal J; Amode, M Ridwan; Aneja, Alisha; Austine-Orimoloye, Olanrewaju; Azov, Andrey G; Barnes, If; Becker, Arne; Bennett, Ruth; Berry, Andrew; Bhai, Jyothish; Bhurji, Simarpreet Kaur; Bignell, Alexandra; et al.
Abstract: Ensembl (https://www.ensembl.org ) has produced high-quality genomic resources for vertebrates and model organisms for more than twenty years. During that time, our resources, services and tools have continually evolved in line with both the publicly available genome data and the downstream research and applications that utilise the Ensembl platform. In recent years we have witnessed a dramatic shift in the genomic landscape. There has been a large increase in the number of high-quality reference genomes through global biodiversity initiatives. In parallel, there have been major advances towards pangenome representations of higher species, where many alternative genome assemblies representing different breeds, cultivars, strains and haplotypes are now available. In order to support these efforts and accelerate downstream research, it is our goal at Ensembl to create high-quality annotations, tools and services for species across the tree of life. Here, we report our resources for popular reference genomes, the dramatic growth of our annotations (including haplotypes from the first human pangenome graphs), updates to the Ensembl Variant Effect Predictor (VEP), interactive protein structure predictions from AlphaFold DB, and the beta release of our new website.